'Half of who you are': Parent and child reflections on the emotional experiences of reversing familial language shift. (April 2023) - Little, Sabine
Aims and objectives: The study explores the emotional experiences of a mother and son during the re-introduction of the heritage language at age 6, following a 2-year hiatus. In particular, it seeks to highlight the affordances of a collaborative, emotionally sensitive approach to family language policy, with parent and child jointly incorporating and acknowledging aspects of the child's identity development. Methodology: Adopting an autoethnographic approach, mother and son kept a joint research diary where critical incidents (as chosen by either one or both) were written down as verbatim as possible, and subsequently reflected on together, with reflections again entered into the diary. Data and analysis: Data were coded according to various emotions (frustration, pride, joy, love, guilt, etc.) as well as a code linked to identity development. These were then thematically analysed. Findings and conclusion: Parent–child collaboration and facilitation of child agency have a positive impact on a child's attitude towards learning the heritage language. Jointly sharing and reflecting on the emotional journey of growing up bilingual and bringing up a bilingual child affords both parent and child an insight into each other's concerns, charting a path towards a collaborative approach to family language policy development. Originality: The study is the first officially documented long-term study focusing on the reversal of familial language shift which provides emotional and language-related data from both parent and child, as part of a complex tapestry of emotion, identity, language, and parent–child relationship. Significance and Implications: Recommendations are made for children to be more actively involved in family language policy research, taking into account their emotional links to, and experiences with, various aspects of language use. In addition, a focus on emotions can assist in a better understanding of the links between language and identity, giving children and parents the space to reflect on and articulate their different points of view, shaping family language policy.